(untitled) (Research, Society and Development, 2023)
Maxillofacial trauma is often related to traumatic dental injuries at the level of the root crown and/or socket. The aim of this study was to carry out an integrative literature review on tooth loss and fractures in patients who are victims of facial trauma, identifying oral rehabilitation strategies, mean time for this and determining factors. An integrative literature review was carried out by searching for scientific articles in the electronic databases PubMed, ScienceDirect and BVS, using the descriptors Tooth Avulsion, Tooth Fractures, Malocclusion, Maxillofacial Injuries and Mouth Rehabilitation, indexed in the period from 2018 to 2022 that they were randomized clinical trials, cohorts, case-control, case reports, book chapters, theses, dissertations and monographs and excluding in vitro, in vivo studies, through the relationship between the terms “AND” and “OR”. After analyzing the eligibility criteria, 8 publications were included for full reading. Studies have shown that post-traumatic rehabilitation treatment requires a multidisciplinary approach due to its challenging nature. Dental fractures have a prognosis and treatments that vary, depending mainly on the location of the fracture and the age of the patient. The rehabilitative alternative that proved to be the most successful for missing teeth was the fixed prosthesis supported by corticobasal implants, based on the average time taken to complete the case, favorable aesthetics and function, and level of patient satisfaction.